2020
DOI: 10.1080/15592324.2020.1823120
|View full text |Cite
|
Sign up to set email alerts
|

Plant defensin expression triggered by fungal pathogen invasion depends on EDR1 protein kinase and ORA59 transcription factor in Arabidopsis thaliana

Abstract: Arabidopsis thaliana exhibits durable 'non-host' resistance against the hemibiotrophic fungal pathogen Colletotrichum tropicale that infects mulberry plants. Arabidopsis non-host resistance comprises two layers of defense: preinvasive and postinvasive resistance. The EDR1 protein kinase contributes to Arabidopsis preinvasive resistance against C. tropicale by inducing the expression of plant defensin (PDF) genes. Here we report that the expressions of multiple PDF genes were strongly induced in Arabidopsis upo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…Bars, 200 lm. at 17 hpi in pen2, which is defective in pre-invasive resistance against Ctro, but not in WT Col-0, indicating strong induction of PDF1.2a by Ctro invasion, consistent with our recent report (Kosaka et al, 2020). Notably, we found that PDF1.2a expression at 17 hpi with Ctro was completely abolished in both clf mutants (Figure 5a).…”
Section: Clf Contributes To the Induced Expression Of Multiple Plant Defensin Genes By Positively Controlling Ora59 Expression Upon Pathosupporting
confidence: 92%
See 2 more Smart Citations
“…Bars, 200 lm. at 17 hpi in pen2, which is defective in pre-invasive resistance against Ctro, but not in WT Col-0, indicating strong induction of PDF1.2a by Ctro invasion, consistent with our recent report (Kosaka et al, 2020). Notably, we found that PDF1.2a expression at 17 hpi with Ctro was completely abolished in both clf mutants (Figure 5a).…”
Section: Clf Contributes To the Induced Expression Of Multiple Plant Defensin Genes By Positively Controlling Ora59 Expression Upon Pathosupporting
confidence: 92%
“…These results indicate that CLF is involved in the induced expression of multiple PDF genes in both pre-invasive and postinvasive resistance against Ctro. We have recently reported that ORA59 and EDR1 are required for the induced expression of PDF genes upon invasion of Ctro (Kosaka et al, 2020). In agreement with this, the Ctro invasion-triggered induction of PDF1.2a at 17 hpi was eliminated in both edr1 and pen2 ora59 mutants (Figure 5a) (note that the ora59 single mutant is not defective in pre-invasive resistance against Ctro).…”
Section: Clf Contributes To the Induced Expression Of Multiple Plant Defensin Genes By Positively Controlling Ora59 Expression Upon Pathosupporting
confidence: 79%
See 1 more Smart Citation
“…For example, foliar application of the endophytic fungus Colletotrichum tropicale reduced Phytophthora infection in the Cacao tree ( Theobroma cacao) [ 39 ]. The reduction in Phytophthora infection could be attributed to the induction of defense-related pathways, as inoculation with C. tropicale triggered several components of the ethylene (ET) defense pathway and induced several disease-related genes in T. cacao and Arabidopsis thaliana [ 40 , 41 ].…”
Section: Endophytes Modulate Plant Defense Responsesmentioning
confidence: 99%
“…For instance, a recent study reported that Arabidopsis CLF, a PRC2 component, is positively required for the expression of ORA59 , a stress-responsive AP2/ERF transcription factor. The reduced ORA59 expression in a clf mutant results in at least a partial defect in leaf immunity because of the low expression of defense-related genes such as PDF1.2a ( Kosaka et al., 2020 ; Singkaravanit-Ogawa et al., 2021 ). On the contrary, in our study using B. rapa , ORA59 was upregulated in the brclf mutant compared with that in the R-o-18 wild type; furthermore, H3K27me3 was densely enriched in the ORA59 chromatin region ( Figure 4B ; Supplementary Figure S9 ).…”
Section: Discussionmentioning
confidence: 99%